EFEKTIVITAS PENGGUNAAN MEDIA KARAMI (KARTU RAHASIA KIMIA) TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI HIDROKARBON KELAS XI IPA MAN KUBU RAYA - Rima Oktavianita; Dedeh Kurniasih; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2019)
This research is motivated by the low activity and learning outcomes of students in MAN Kubu Raya, especially in Hydrocarbon Material of Chemistry Subject due to lack of students’ understanding about the concept of Hydrocarbon. Therefore, it is needed to use a learning media in accordance with the characteristics of the material and students who are expected to improve students’ learning activities and outcomes. This research aimed to find out whether there were differences in students’ activities and learning outcomes also the effectiveness of using the Chemistry Secret Card Media (KARAMI) on the activities and learning outcomes between students taught by using KARAMI and students taught without using the media. This current research was in form of Quasy Experimental design with the Nonequivalent Control Group Design. The sample was selected by using purposive sampling technique that were XI Science 2 as the experimental class and XI Science 3 as the control class. The technique of collecting data in this research used observation sheets, learning outcomes tests (pretest-posttest) and interviews. Based on the data analysis by using non parametric statistical test, U-Mann Whitney, showed that there were differences in learning activities, 0,00